PREVALENCE AND RISK FACTORS FOR VITAMIN D DEFICIENCY IN OVERWEIGHT AND OBESE ADOLESCENTS IN UKRAINE - Shulhai, A-M. A.; Pavlyshyn, H. A. (International Journal of Medicine and Medical Research, 2019)
Background. Vitamin D affects the function of many organs and systems. Lipid metabolism disorder is established to be one of the risk factors for vitamin D deficiency, and the amount of adipose tissue is crucial. Objective. The aim of the study was to determine the prevalence and risk factors for vitamin D deficiency in overweight and obese adolescents. Methods. 146 children with excessive weight and obesity as well as 63 healthy children with normal body weight were examined. In the study groups, there were no children taking vitamin D. Vitamin D status was evaluated by the level of 25(OH)D in blood serum. Vitamin D deficiency was diagnosed at the level of 25(OH)D between 20 and 29 ng/ml, and significant deficiency – below 20 ng/ml, normal calcidiol content was 30-100 ng/ml. Results. The average level of 25(OH)D in the adolescents with normal body weight was 19.76±4.28 ng/ml, in the adolescents with excessive body weight – 15.24±3.47 ng/ml, and in the obese children – 13.87±2.71 ng/ml. The prevalence of vitamin D deficiency in the overweight adolescents was 70.62%, and in the adolescents with obesity – 77.19%. Conclusions. Vitamin D deficiency is prevalent in the adolescents with overweight and obesity. To prevent the development of hypovitaminosis and vitamin D deficiency, it is necessary to carry out educational activities with adolescents for promotion of healthy lifestyle and healthy food, as well as to develop an optimal program for improving vitamin D status in the obese children.